Knowledge and Attitude of Women regarding Safe Abortion in Pokhara Metropolitan City - Thapaliya, Rekha; Gurung, Bandi; Shrestha, Saphalta; Poudel, Usha Kiran; Shrestha, Sabina (Journal of Karnali Academy of Health Sciences, 2024)
Background: Safe abortion is a very crucial part of reproductive health service. Women with adequate knowledge on safe abortion tended to have more liberal attitudes towards access to safe abortion services. The objective of the study is to find out knowledge and attitude of women regarding safe abortion in Pokhara Metropolitan City. Method: Descriptive cross sectional research design was adopted. Probability simple random sampling technique was used to select 374 women between the age group of 20 to 49 years residing in Pokhara Metropolitan City. Face to face interview technique with structured interview schedule was used. The data was analyzed by using descriptive and inferential statistics (Chi square test). Results: Out of 374 women 68.7% were aged 40 and above. The mean age of the women was 30.39 years, with a standard deviation of 7.35 years. Among them 72.2% were Hindu, 70.6% were married. Cent percent of them were literate. In the present study, 66.5% of the women were multigravida, 41.7% had two living children and 16.6% had history of abortion. In this study, 35.8% of the women had good knowledge and 52.1% had positive attitude towards safe abortion. Conclusions: It is concluded that more than half of the women had poor knowledge but positive attitude on safe abortion. In order to increase the level of knowledge and attitude of women, awareness raising programme on safe abortion should be conducted through concerned authority.